Hnací ústrojí řadového čtyřválcového zážehového motoru - Mačuga, Martin (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2008)
Dle daného vrtání válce, zdvihu a ideálního indikátorového diagramu budeme zjišťovat maximální tlak ve válci a dále navrhovat rozměry pístní skupiny ( pístu a pístního čepu) a také ojnice. Pak budeme provádět pevnostní výpočet horního oka ojnice dle daných výpočtů a to pro zvolený materiál ojnice. Zvolený materiál nakonec vyhodnotíme zda je pro navrhovanou ojnici vhodný.

According to given to cylinder diameter, stroke and ideal indicator diagram we will investigate with maximum cylinder pressure and further design for proportions piston insider ( piston and piston - pin) as well as piston rod. Then shall do strength calculation upper connecting-rod eye according to given to calculations namely for the select material of piston rod. In the end we evaluate the select material whether is for suggested piston rod fit.
Powertrain of in-line four-cylinder spark ignition engine
Keywords: vrtání; zdvih; ideální indikátorový diagram; maximální tlak; píst; pístní čep; ojnice.; cylinder diameter; stroke; ideal indicator diagram; maximum cylinder pressure; piston; piston – pin; piston rod